Impact of Finance Technology on Profit at Sharia Banks in Bandung - Wati Aris Astuti (International Journal of Research and Applied Technology (INJURATECH), 2022)
Industry 4.0 is currently giving rise to an innovation in all fields. One of them is the financial services sector by combining application-based funding technology. Innovations in financial services that are currently trending related to access to financial products are known as Financial Technology (FinTech). The purpose of this study is to analyse whether there are differences in earnings before and after the existence of Financial Technology in Islamic Banks. The research method used is descriptive quantitative in the form of a comparison that aims to measure the influence before and after the existence of FinTech on Profits at Islamic Banks for the 2017-2020 period as measured by Net Interest Margin, the population of this study from financial statements which was then narrowed down using purposive sampling so that the sample in this study are the quarterly financial statements of Islamic banks for the period 2017-2020. The results of the study show that in Islamic banks there is no significant effect on the net interest margin before and after using fintech, this is due to several factors including the level of security, long-term maintenance and the bank's ability to maintain internet banking are also experiencing problems. The not yet maximal use of internet banking in Indonesia for banking transactions is also still an obstacle to the development of internet banking services.